A inelegibilidade pela reprovação de contas prevista no art. 1°., inciso I, alínea G, da Lei Complementar n°. 64/1990 - Silva Júnior, Aroldo Campos da (2025)
Theme. This research deals with the analysis of ineligibility due to the rendering of accounts provided for in item g, section I, of Complementary Law No. 64/1990. Problem. As a research problem, the following question is asked: does the analysis criterion of the Superior Electoral Court to declare ineligibility expressed in item g, section I, of Complementary Law No. 64/1990 comply with constitutional principles expressed in the Brazilian legal system, such as the principles of due process of law and the natural judge? Hypothesis. The research is based on the following hypothesis: the judgment in theory exercised by the Superior Electoral Court to declare ineligibility based on item g, section I, of Complementary Law No. 64/1990, restricts the constitutional principles of the due process of law and the natural judge. Objective. The objective of this research is to study the foundations that establish the decisionmaking process of ineligibility provided for in item g, section I, of Complementary Law No. 64/1990 and its assumptions, establishing the normative standards that support the declaratory process established by the Superior Electoral Court to declare the ineligibility that is the object of the research. Methodology. The deductive method is used to develop the study, through academic research which approach is qualitative, bibliographic and documentary through the doctrinal and jurisprudential examination on the ineligibility contained in item g, section I, of Complementary Law No. 64/1990. Conclusion. The research concludes that the procedure adopted by the Superior Electoral Court to declare the ineligibility provided for in article 1, paragraph I, item g, of Complementary Law n° 64/90 is unconstitutional and that the principles of due process of law, the natural judge and administrative probity by the specialized courts and the Brazilian Constitutional Court needs to been reinterpreted